Administration of isoferulic acid improved the survival rate of lethal influenza virus pneumonia in mice - Shinya Sakai; Hiroshi Ochiai; Naoki Mantani; Toshiaki Kogure; Naotoshi Shibahara; Katsutoshi Terasawa (Hindawi Limited, 2001)
Background: Isoferulic acid (IFA) is a main active ingredient of the rhizoma of Cimicifuga heracleifolia, which is used frequently in Japanese traditional medicine as an anti-inflammatory drug. It has been revealed that IFA inhibits the production of macrophage inflammatory protein-2 (MIP-2), which is a murine counterpart of the chemokine family that may contribute to the pathogenesis of inflammatory diseases through the chemotactic activity for inflammatory and immune effector cells.